ADMISSIBILITY OF NARCO-ANALYSIS FOR FORENSIC INVESTIGATION IN THE COURT OF LAW: CRIMINOLOGICAL PERSPECTIVE IN INDIAN SCENARIO (Journal of Forensic Medicine & Toxicology, 2022)
In the present changing ethos around the world, the individual started to glance through their place in the space of simplicity, and for this, it needs a strong economy, regulative issues, and a lifestyle. This drives immense competition among everyone, and people started using more current innovations in every sector so one will constantly administer others. The criminal value framework isn’t any more special than various frameworks and it has similarly been impacted by new mechanical movements.This study constitutes the methods and procedures used for the identification of criminal and criminalistic behaviour through Narco-examination, lie detector, and brain mapping. As criminals have begun utilizing techniques for covering up and carrying out allegations of unpredictable cases with conventional strategies. There is a need to authenticate the technologies in the criminal system. Through, the present study endeavoured to investigate the issues and imperative choices of the Judiciary which influenced the criminal equity system in India.
Keywords: Narco-Analysis; Psychology; Sodium Pentothal; Sodium Amytal; Scopolamine; Psychotherapeutic Drugs; Psychological Techniques; Criminal Equity System